2001
DOI: 10.1161/01.cir.103.8.1083
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Pentoxifylline in Patients With Idiopathic Dilated Cardiomyopathy Treated With Angiotensin-Converting Enzyme Inhibitors and Carvedilol

Abstract: In patients with idiopathic dilated cardiomyopathy, the addition of pentoxifylline to treatment with digoxin, ACE inhibitors, and carvedilol is associated with a significant improvement in symptoms and left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 36 publications
5
74
1
4
Order By: Relevance
“…[20] which included patients with idiopathic cardiomyopathy. In these studies, treatment with pentoxifylline was not associated with significant changes in TNF-alpha [20,30] and IL-6 [20] concentrations. Significant improvements in symptoms and left ventricular function were seen in one trial [30] but not the other [20].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…[20] which included patients with idiopathic cardiomyopathy. In these studies, treatment with pentoxifylline was not associated with significant changes in TNF-alpha [20,30] and IL-6 [20] concentrations. Significant improvements in symptoms and left ventricular function were seen in one trial [30] but not the other [20].…”
Section: Discussionmentioning
confidence: 63%
“…In these studies, treatment with pentoxifylline was not associated with significant changes in TNF-alpha [20,30] and IL-6 [20] concentrations. Significant improvements in symptoms and left ventricular function were seen in one trial [30] but not the other [20]. However in this negative study, the results are complicated by the fact patients in this study were treated with a beta-blocker (carvedilol) for the 3 months prior to initiation of pentoxifylline therapy.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, it has been proven that it increases red blood cell flexibility, reduces blood viscosity and decreases platelet aggregation. PTX it is commonly used for the treatment of intermittent claudication in Western countries and several small clinical trials have reported beneficial effects of PTX supplementation on multiple surrogate clinical markers in subjects with chronic heart failure [128][129][130][131] . Indeed, recent evidences showed that PTX can decrease free-radical-mediated lipid oxidation and can improve histological features of NASH [132,133] , such as steatosis, lobular inflammation and fibrosis.…”
Section: Other Anti-oxidant Drugsmentioning
confidence: 99%
“…Na cardiomiopatia dilatada com IC crônica e na cardiomiopatia periparto, a utilização de pentoxifilina na posologia de 1200mg a 2400mg/dia, pelo período de seis meses, ocasionou melhora clínica da classe funcional e da função ventricular (tabela 15). Esses resultados sugerem um papel benéfico da pentoxifilina como terapêutica coadjuvante nas cardiomiopatias inflamatórias crônicas, sendo ainda necessário ainda comprovar este benefício nas cardiomiopatias de início recente ou miocardites agudas [118][119][120][121] . Os pacientes que se encontram na fase aguda de miocardite podem desenvolver tanto taquiarritmias como bradiarritmias.…”
Section: Imunomodulaçãounclassified